Answer:
t74 = 674
Step-by-step explanation:
Givens
n = 74
a = 17
d = 26 - 17 = 9
Formula
tn = a + (n - 1)* d
Solution
tn = 17 + 73 * 9
tn = 17 + 657
tn = 674
Remark: This is an application of the arithmetic formula for the "last" term.
You pretty much have to know to to juggle the parts as this one was done.
[tex]\huge\bf\underline{\underline{\pink{A}\orange{N}\blue{S}\green{W}\red{E}\purple{R:-}}}[/tex]
Here we have,
[tex]\mapsto\tt{t_n = a + (n - 1) \times d} \\ \\ \mapsto\tt{t_n = 17 + (74 - 1) \times 9} \\ \\ \mapsto\tt{t_n = 17 + 73 \times 9} \\ \\ \mapsto\tt{t_n = 17 + 657} \\ \\ \mapsto\tt{t_n = 674}[/tex]